The Epidemiology of Zoonotic Brucellosis in Bahr el Ghazal Region of South Sudan - Madut, Nuol Aywel; Muleme, James; Kankya, Clovice; Nasinyama, George William; Muma, John Bwalya; Godfroid, Jacques; Jubara, Ambrose Samuel; Muwonge, Adrian (Frontiers in Public Health, 2019)
Background: In this study, we focused on three zoonotic brucellosis risk groups; abattoir workers, febrile cases at Wau hospital and cattle herders, in Wau South Sudan. Competitive c-ELISA was used to detect anti-Brucella antibodies in 725 individuals between December 2015 and May 2016. In addition, questionnaire metadata, focus group discussions and key informant interviews were used to characterize the epidemiology of zoonotic brucellosis in this region. Results: Overall, we estimate 27.2 % (95% CI=23.9-30.6) brucellosis sero-prevalence; 32.1 % (95% CI=26.2-38.4), 23.0% (95% CI=19.1-27.4) and 34.6% (95% CI=24.4-46.3) among abattoir workers, febrile cases and herders respectively. Marital status (Single, OR=0.58, 95%CI: 0.36-0.91, P=0.02) and ethnicity (Kerash OR=6.01, 95%CI: 1.97-21.10, P=0.003 and Balanda, OR=3.78, 95%CI: 1.42-12.02, P=0.01) were associated with brucellosis. While gender and ethnicity were important factors for general awareness of zoonotic diseases. Highly ranked occupations at risk included veterinarian, butchers and milk handlers. We also identified covariate patterns for clinical diagnostics and public health interventions. Conclusion: We report the highest sero-prevalence of zoonotic brucellosis in three risk groups in the East African region. All this is not only occurring in a population with limited awareness that brucellosis is a zoonotic disease but also where one in nine health workers tested was sero-positive. We identified social demographic associations with brucellosis, however, the qualitative analysis suggests these are more complex and nuanced. Therefore, future studies could benefit from the use of the mixed methods approach to add extensiveness and depth to our understanding of zoonotic disease drivers, in order to implement mitigating measures such as cattle vaccination.